Metagenomics reveals the response of desert steppe microbial communities and carbon-nitrogen cycling functional genes to nitrogen deposition - Ye, He; Zhao, Yu; He, Shilong; Wu, Zhendan; Yue, Mei; Hong, Mei (Frontiers in Microbiology, 2024)
Nitrogen (N) deposition seriously affects the function of carbon (C) and N cycling in terrestrial ecosystems by altering soil microbial communities, especially in desert steppe ecosystems. However, there is a need for a comprehensive understanding of how microorganisms involved in each C and N cycle process respond to N deposition. In this study, shotgun metagenome sequencing was used to investigate variations in soil C and N cycling-related genes in the desert steppe in northern China after six years of the following N deposition: N0 (control); N30 (N addition 30 kg ha -1 yr -1 ): N50 (N addition 50 kg ha -1 yr -1 ). N deposition significantly increased the relative abundance of Actinobacteria (P < 0.05) while significantly decreased the relative abundances of Proteobacteria and Acidobacteria (P < 0.05). This significantly impacted the microbial community composition in desert steppe soils. The annual addition or deposition of 50 kg ha -1 yr -1 for up to 6 years did not affect the C cycle gene abundance but changed the C cycle-related microorganism community structure. The process of the N cycle in the desert steppe was affected by N deposition (50 kg ha -1 yr -1 ), which increased the abundance of the pmoA-amoA gene related to nitrification and the nirB gene associated with assimilation nitrite reductase. There may be a niche overlap between microorganisms involved in the same C and N cycling processes. This study provides new insights into the effects of N deposition on soil microbial communities and functions in desert steppe and a better understanding of the ecological consequences of anthropogenic N addition.